Mitoxantrone modulates a heparan sulfate-spike complex to inhibit SARS-CoV-2 infection - Qi Zhang; Peter Radvak; Juhyung Lee; Yue Xu; Vivian Cao-Dao; Miao Xu; Wei Zheng; Catherine Z. Chen; Hang Xie; Yihong Ye (Scientific Reports, 2022)
Abstract Spike-mediated entry of SARS-CoV-2 into human airway epithelial cells is an attractive therapeutic target for COVID-19. In addition to protein receptors, the SARS-CoV-2 spike (S) protein also interacts with heparan sulfate, a negatively charged glycosaminoglycan (GAG) attached to certain membrane proteins on the cell surface. This interaction facilitates the engagement of spike with a downstream receptor to promote viral entry. Here, we show that Mitoxantrone, an FDA-approved topoisomerase inhibitor, targets a heparan sulfate-spike complex to compromise the fusogenic function of spike in viral entry. As a single agent, Mitoxantrone inhibits the infection of an authentic SARS-CoV-2 strain in a cell-based model and in human lung EpiAirway 3D tissues. Gene expression profiling supports the plasma membrane as a major target of Mitoxantrone but also underscores an undesired activity targeting nucleosome dynamics. We propose that Mitoxantrone analogs bearing similar heparan sulfate-binding activities but with reduced affinity for DNA topoisomerases may offer an alternative therapy to overcome breakthrough infections in the post-vaccine era.